THE INFLUENCE OF ENTREPRENEURIAL MARKETING ON THE LOCAL CULINARY UMKM INDUSTRY IN MAKASSAR CITY - Muh Syulhasbiullah; Michael Ricky Sondak (RADJA PUBLIKA, 2025)
The purpose of this research is to examine how certain aspects of entrepreneurial marketing (EM) affect the success of MSMEs in the food service industry in Makassar City. Data were analyzed using Structural Equation Modeling (SEM) with Smart-PLS. The study approach included administering a questionnaire using a five-point Likert scale. One hundred sixty-seven culinary MSMEs were chosen at random for the study. From what we can see, EM has a significant and positive impact on the production, market, inventive, and financial performance of MSMEs in the culinary industry. The analysis's T-statistic and P-value demonstrate that EM boosts performance in producing (O=0.931, T=78.263, P=0.000), selling (O=0.897, T=52.661, P=0.000), coming up with new ideas (O=0.885, T=38.155, P=0.000), and managing money (O=0.622, T=10.792, P=0.000). To be clear, neither market performance nor innovation performance has a statistically significant impact on financial outcomes. Findings suggest that MSMEs in the culinary industry in Makassar City would fare better if they make good use of EM. For these micro, small, and medium-sized enterprises (MSMEs) to thrive, they must be creative, aggressive, opportunistic, risk-taking, and focused on their customers. To further investigate the potential effects of EM activities on different performance metrics in culinary MSMEs, future studies should gather data from a broader range of locales. Furthermore, it is essential to study how big culinary enterprises use EM and to find out what techniques culinary MSMEs use that work.